THE BUGINESE POEMS IN LONTARA (A LITERATURE ANALYSIS) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to describe the improvement in learning outcomes of Bugis poetry writing using the research method in this research is a library research with a qualitative approach to analyze the selected poetry of Gus mus. Literature is an artistic creation full of very interesting expressions and full of entertaining imagination. One of the most interesting and imaginative literary works is poetry. Poetry is a literary work in which it is full of imagination and meaningful expressions of feelings and emotions. Everyone is free to express the expressions and thoughts from life experiences that the poet wants to convey through poetry. So that poetry is very interesting to analyze through the language used. Therefore, the writer is interested in analyzing the poetry of Gus Mus.